Barriers and facilitators to access mental health services among people with mental disorders in Indonesia: A qualitative study - Lafi Munira; Pranee Liamputtong; Pramon Viwattanakulvanid (Belitung Nursing Journal, 2023)
Background: The care and treatment management of people with mental health problems has become a prominent global concern in recent years that requires consistent attention. However, the literature suggests that only a small percentage of individuals with mental health problems in Indonesia receive the necessary mental health care. Therefore, it is crucial to explore this gap.